If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(((x-1)/7)*(2*x-2))/49 = 0
((x-1)*(2*x-2))/(7*49) = 0
( 2*x-2 )
2*x-2 = 0 // + 2
2*x = 2 // : 2
x = 2/2
x = 1
( x-1 )
x-1 = 0 // + 1
x = 1
x in { 1, 1 }
| 3-9x=1-x | | 4(x+5)=2(x-7) | | 17x-2=12x-1 | | y-10=30 | | 4e-3(2e-2)=3(e+8) | | 3(4d-2)=3(d-2) | | 5(c-2)=3(c+6) | | 15x-4+4x+5+65= | | 7(b-4)=5(b-2) | | 2(3b-4)=5(b-1) | | 3(3a+1)=30 | | 4(1/3x-1/4)+4/3x/3+1=6 | | 8-4=6z-8z | | k^3+2k^2-10k-20=0 | | 7(x+2)=7x+10 | | z^4-26z^2+25=0 | | 5x-10-2=13 | | 1/2x16=0 | | p^(2/3)+p^(1/2) | | 3x-7+5=16 | | (x^2-81)/(x^2-6x-27)*(x+3)/x | | 98x+456= | | x^3-4x=85008 | | 250=(50-3)+x | | s=2x+t/r | | x/5-x=1/5 | | 0.5y=30 | | -6(x-2)+4(8x-12)=68 | | 6ln(3x)=12 | | -6(x-2)-4(8x-12)=68 | | 3x-2=7x+8 | | 4(-6+x)=5x+1/4 |